Questionnaires in the design and evaluation of community-oriented technologies. (2017) - Cabitza, Federico; Locoro, Angela
Stimulated by the maturity and ease-of-use of online psychometric questionnaire platforms, in this paper we discuss their exploitation as tools to gather representative indications, collect preferences and elicit requirements from the members of online communities for the design of their web-based technologies. To this practical aim, we suggest an alternative vision to the traditional way of considering questionnaires as part of the quantitative researcher toolbox, or worse yet, a trivial way to collect opinions with no design-oriented value. Rather, we advocate for a qualitative turn in questionnaire design and for the interpretation of the responses collected from even massive communities of prospective users. In particular, we propose to see questionnaires as valuable tools for two related tasks: the collection of preferences for the prioritisation of features and requirements of prospective web-based systems; and the evaluation of the impact of these systems on the communities that adopt them. In particular, this impact is addressed on a multidimensional perspective, including community values such as trust, sense of reciprocity, sense of community and social capital. In both cases, questionnaires are lightweight, feasible and cost-effective tools to enable the incremental improvement of community-oriented technologies according to the direct feedback collected from the community members.